ATP concentration in latex as an indicator for early evaluation of yield in Hevea brasiliensis - Sreelatha, S.; Jacob, James; Mercykutty, V.C.; Simon, Sheela P.; Krishnakumar, R.; Annamalainathan, K. (Journal of Plantation Crops, 2014)
Adenosine 5’ triphosphate (ATP) in the laticiferous tissues of Hevea brasiliensis plays a major role in rubber biosynthesis through its direct involvement in metabolic pathways and indirectly through H+ ATPase activity. A strong positive correlation was observed between dry rubber yield and latex ATP, when ATP was measured in the latex of ten Hevea clones with different yield potentials such as low, medium and high. The latex ATP was significantly high in clones with higher yield than medium and low yielding clones. The correlation between same day latex yield and ATP during the peak yielding season (September-November) also showed a direct relationship. This study was extended to immature plants of the same clones to confirm the practical application of this finding in crop improvement programme. Latex ATP was analysed in two year old young plants and continued for five years to correlate with rubber yield of the mature trees in field trial. A positive correlation was noticed between ATP in young plants and mature tree rubber yield. Young plants of high yielding clones always showed higher latex ATP concentration. In view of the direct relationship with yield, significant differences between clones and its seasonal insensitivity, latex ATP could be used as an indicator for early prediction of high yield in Hevea.